Optimalisasi Tata Letak Fasilitas Koperasi Wanita Cahaya Uma Hasti di Cilodong, Depok - Anita Nurfida; Oktaviani, Anggi (Indonesian Journal for Social Responsibility, 2021)
Koperasi Wanita Cahaya Uma Hasti is a cooperative located in Sukamaju sub-district, Cilodong sub-district, Depok city. This cooperative provides various basic necessities and other household needs. In the arrangement and arrangement of goods sold (display) at the Cahaya Uma Hasti women's cooperative, it is still irregular and inaccurate, making it difficult for customers to retrieve goods. In addition, space utilization is not optimal, making consumers less comfortable. The purpose of this Community Service is to provide an understanding of the optimization of the facility layout and make proposals for the layout of the Cahaya Uma Hasti Depok cooperative facilities to maximize the arrangement of goods sold. The implementation of this activity is carried out in three stages, namely: the preparation, implementation and evaluation stages. The preparatory stage is carried out by direct observation and conducting interviews with all cooperative managers, as well as preparing materials to be delivered at the community service activity. The second stage is the implementation of the activity by holding workshops and discussions on optimizing the layout of the facilities tailored to the needs of the Cahaya Uma Hasti women's cooperative. After that, an evaluation stage of the community service activity is carried out to determine the success of the community service event and solve partner problems. After the proposal for the layout of the Koperasi Wanita Cahaya Uma Hasti's facilities, the following conclusions were obtained: the management and members of the cooperative got knowledge about optimizing the layout of the Koperasi Wanita Cahaya Uma Hasti facility so that it can make it easier for customers to shop and organize goods in the Cahaya Wanita Cooperative. Uma Hasti is maximized and makes it easier for the management to enter goods into the cooperative.